2012
DOI: 10.4319/lo.2012.57.2.0420
|View full text |Cite
|
Sign up to set email alerts
|

Physical control on methanotrophic potential in waters of the Santa Monica Basin, Southern California

Abstract: Methane concentrations and turnover rates were measured throughout the water column at nine stations in the Santa Monica Basin (SMB), at one station in the San Pedro Basin (SPB), and at one station in the Santa Catalina Basin (SCtB) in July 2007 and September 2009. Methane concentrations were elevated throughout the water column, with subsurface (4-15 nmol L 21 ), midwater (7.5-100 nmol L 21 ), and bottom-water (5-242 nmol L 21 ) maxima. The SMB water column was divided into four depth-dependent regimes, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…However, our rates are 3 orders of magnitude lower compared to the measurements conducted after the Deep Water Horizon accident in the Gulf of Mexico, during which catastrophic amounts of hydrocarbons were released into the water column, triggering a rapid response in MO x activity (Valentine et al, 2010;Kessler et al, 2011). Other MO x rate measurements were conducted in Bristol Bay and the southeast Bering Sea (Griffith et al, 1982), the Cariaco Basin (Ward et al, 1987), Saanich Inlet (Ward, 1989 andWard andKilpatrick, 1990), in Southern California Bight (Ward, 1992;Pack et al, 2011;Heintz et al, 2012;Ward and Kilpatrick, 1993), in the Eel River basin (Valentine et al, 2001), the Gulf of Mexico (Kelley, 2003), and at hydrothermal vents at Juan de Fuca Ridge (de Angelis et al, 1991(de Angelis et al, , 1993). It appears that most of these MO x rates fall into the range between 0.001 and 10 nM day −1 and that MO x activity is elevated in ocean environments with high CH 4 concentrations.…”
Section: Vertical Distribution Of Methane Oxidationmentioning
confidence: 59%
See 1 more Smart Citation
“…However, our rates are 3 orders of magnitude lower compared to the measurements conducted after the Deep Water Horizon accident in the Gulf of Mexico, during which catastrophic amounts of hydrocarbons were released into the water column, triggering a rapid response in MO x activity (Valentine et al, 2010;Kessler et al, 2011). Other MO x rate measurements were conducted in Bristol Bay and the southeast Bering Sea (Griffith et al, 1982), the Cariaco Basin (Ward et al, 1987), Saanich Inlet (Ward, 1989 andWard andKilpatrick, 1990), in Southern California Bight (Ward, 1992;Pack et al, 2011;Heintz et al, 2012;Ward and Kilpatrick, 1993), in the Eel River basin (Valentine et al, 2001), the Gulf of Mexico (Kelley, 2003), and at hydrothermal vents at Juan de Fuca Ridge (de Angelis et al, 1991(de Angelis et al, , 1993). It appears that most of these MO x rates fall into the range between 0.001 and 10 nM day −1 and that MO x activity is elevated in ocean environments with high CH 4 concentrations.…”
Section: Vertical Distribution Of Methane Oxidationmentioning
confidence: 59%
“…Range of methane oxidation rates measured at different locations in the ocean water column derived from tracer incubations using 3 H-CH 4 (Reeburgh et al, 1991;Valentine et al, 2001Valentine et al, , 2010Heintz et al, 2012 …”
Section: Figmentioning
confidence: 99%
“…It was calculated as the inverse of the ratio (r), corrected for the incubation time (t). Thus, this parameter is independent of the ambient methane concentration, and gives a good measure of the methanotrophic potential (Heintz et al, 2012).…”
Section: Methane Oxidation (Mox) Ratementioning
confidence: 99%
“…In contrast, the low levels of CH 4 found in the Amundsen Basin may be related to CH 4 oxidation through methanotrophic activity. In fact, Heintz et al (2012) showed that methane oxidation rates below 700 m in the Santa Monica Basin were between 0.12 and 1.35 nmol L −1 d −1 . Aerobic CH 4 oxidation is known to be performed by methanotrophic bacteria (MOB), typically belonging to the Gamma-(type I) or Alphaproteobacteria (type II) (Hanson and Hanson, 1996;Murrell, 2010).…”
Section: Aiw and Adwmentioning
confidence: 99%